2013
DOI: 10.1103/physrevb.87.125415
|View full text |Cite
|
Sign up to set email alerts
|

Phonon softening and direct to indirect band gap crossover in strained single-layer MoSe2

Abstract: Motivated by recent experimental observations of Tongay et al. [Nano Lett. 12, 5576 (2012)] we show how the electronic properties and Raman characteristics of single layer MoSe 2 are affected by elastic biaxial strain. We found that with increasing strain: (1) the E and E Raman peaks (E 2g and E 1g in bulk) exhibit significant redshifts (up to ∼30 cm −1 ), (2) the position of the A 1 peak remains at ∼180 cm −1 (A 1g in bulk) and does not change considerably with further strain, (3) the dispersion of low energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
156
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(176 citation statements)
references
References 42 publications
20
156
0
Order By: Relevance
“…Increase in the in-plane lattice constant by ∆a leads to reduction of direct and indirect transition energies at a different rate (Figure 2a and d) in agreement with the previous studies 16,18,19,24,30,31 . The changes are more pronounced for transitions involving the K point.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Increase in the in-plane lattice constant by ∆a leads to reduction of direct and indirect transition energies at a different rate (Figure 2a and d) in agreement with the previous studies 16,18,19,24,30,31 . The changes are more pronounced for transitions involving the K point.…”
Section: Resultssupporting
confidence: 92%
“…The indirect-to-direct crossover in these MX 2 compounds (M=Mo,W and X=S,Se) results from local shift of valence band hills and conduction band valleys in the Brillouin zone 4,7,9,10,[16][17][18][19] . In single layers, the conduction band minimum (CBM) and valence band minimum (VBM) coinciding at the K point, making them direct gap semiconductors.…”
mentioning
confidence: 99%
“…55 Previously we showed that electronic band structure of single-layer MoSe 2 undergoes a direct to indirect band gap crossover under tensile strain. 56 Moreover, strain induced phase transition (from semiconducting 2H phase to metallic 1T' phase) is observed in MoTe 2 . 57 Therefore, in contrast to typical ultra-thin materials, monolayer CdTe exhibits robust and moderate band gap that covers the broad range of the solar spectrum, which are essential for its utilization in future electronics.…”
Section: Strain Response Of Single-layer Cdtementioning
confidence: 99%
“…For TMDs, a number of DFT calculations have studied the dependence of the band structure and phonon modes with external strain [51,53,121,[123][124][125][126][127][128][129][130], and the consequences on different physical properties have been discussed in Refs. [131][132][133].…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%